IMPLEMENTASI ASAS KESEIMBANGAN DALAM TRANSAKSI JUAL BELI TANAH - Windi Arista (Justici, 2022)
ABSTRACT An agreement is an agreement in which two or more people bind themselves to carry out something in the field of property. In the case of a land sale and purchase agreement, problems often occur, one of which is caused by the imbalance of the parties in the contract agreement. The principle of balance is reflected when the parties who will make the agreement are given freedom based on Article 1338 of the Civil Code. The freedoms referred to in Article 1338 of the Civil Code are not absolute, but must be balanced with rules stating that these freedoms are allowed as long as they do not conflict with the law, propriety and custom, decency and public order in their implementation and implementation. The problem in this paper is about how to apply the principle of balance in a land sale and purchase contract. The type of research that the author uses is normative legal research, which is a legal research method carried out by examining library materials or secondary data. The application of the principle of balance in the land sale and purchase agreement is reflected in Article 1320 of the Civil Code paragraph (1). In addition, the application of the principle of balance is described in the formulation of the rights and obligations of the parties, as a determining indicator the translation appears to be in a balanced position between the rights and obligations of each party in the land sale and purchase agreement.